Clinicians' perspectives of a care coordination model for children with medical complexity - Munn, Emily E.; Griffin, Jake W.; Ramly, Edmond; Ciccarelli, Mary R.; Pangelinan, Melissa M. (Frontiers in Pediatrics, 2025)
BackgroundThe Indiana Complex Care Coordination Collaborative (IC4) is a statewide initiative designed to enhance care for children with medical complexity (CMC) by embedding nurse care coordinators within clinical practices. This study explored clinicians' perspectives on how these coordinators influenced care delivery.MethodsFourteen clinicians from six participating medical systems completed semi-structured interviews. Discussions focused on the impact of care coordinators on workflow, patient care, clinician workload, and the medical home experience. Transcripts were analyzed using an inductive approach to identify key themes and insights.ResultsClinicians consistently described care coordinators as central to improving communication and access for families, serving as a reliable point of contact, and facilitating smoother interactions with the healthcare system. They noted that care coordinators helped organize patient information, enabling focused and efficient clinical encounters. This support reduced administrative burden and allowed clinicians to prioritize patient needs more effectively. Additionally, care coordinators played a vital role in educating staff, advocating for families, and addressing both medical and non-medical concerns. While clinicians emphasized the value of care coordination, they also highlighted the need for clearer role definitions and adequate training to ensure coordinators are fully integrated and utilized appropriately.ConclusionClinicians reported that embedded care coordinators significantly enhanced the quality, efficiency, and responsiveness of care for CMC. Their perspectives underscore the importance of structured, well-supported care coordination to improve clinical practice and patient outcomes.